Psychometric validation of the Child Healthy Lifestyle Profile in South Korea: a cross-sectional study - Kyung-Ah Kang; Shin-Jeong Kim (Child Health Nursing Research, 2023)
Purpose This study aimed to validate the Child Healthy Lifestyle Profile as an instrument for screening healthy behaviors in school-aged children in South Korea. Methods Self-reported questionnaires were administered to 454 students, comprising elementary-school students (n=221) and child cancer survivors (n=233). Reliability and validity were assessed using Cronbach's ⍺, exploratory factor analysis (EFA), and confirmatory factor analysis (CFA). Results Cronbach's ⍺, as a reliability test, was 0.87. Varimax rotation yielded nine factors with eigenvalues greater than 1 in the EFA, which explained 61.0% of the total variance. In the CFA, both convergent and discriminant validities were acceptable. Therefore, the Child Healthy Lifestyle Profile was validated as an assessment tool for Korean school-aged children. Conclusion Based on the results of this study, the Child Healthy Lifestyle Profile was identified as a reliable and valid instrument for assessing healthy lifestyles in elementary-school children in South Korea.